Explosive instability in the plasma-beam systems - Buts, V.A.; Koval’chuk, I.K. (Вопросы атомной науки и техники, 2012)
The results of investigation of explosive instability in the plasma-beam systems are presented. It has been shown that in the general case, the dynamics of this instability can be essentially changed, right up to its full suppression, if one takes into account a fast beam wave (wave with positive energy). The parameters when explosive instability is realized and when it is suppressed are defined. It was shown that in the case of such four wave interaction there are regimes with attributes of irregularity. Представлены результаты исследования динамики взрывной неустойчивости в плазменно-пучковых системах. Показано, что в общем случае учет быстрой пучковой волны (волны с положительной энергией) может существенно менять динамику этой неустойчивости, вплоть до ее срыва. Определены параметры, при которых реализуется взрывная неустойчивость, и параметры, при которых происходит ее подавление. Показано, что при таком четырехволновом взаимодействии существуют режимы с признаками нерегулярности. Представлені результати дослідження динаміки вибухової нестійкості в плазмово-пучкових системах. Показано, що в загальному випадку врахування швидкої пучкової хвилі (хвилі з позитивною енергією) може істотно змінити динаміку цієї нестійкості, навіть до зриву. Визначені параметри, при яких реалізується вибухова нестійкість, та параметри, при яких виникає її зрив. Показано, що при такій чотирьоххвилевій взаємодії існують режими з ознаками нерегулярності.